A6.19 Non-canonical NF-κB signalling in endothelial cells promotes angiogenesis in a novel 3D model of rheumatoid arthritis synovial angiogenesis. (13th February 2015) - Maracle, CX; Helder, B; Noort, AR; van der Horst, C; Tas, SW
Abstract : Background: Angiogenesis is a crucial mediator in rheumatoid arthritis (RA) pathogenesis. Current in vitro models of angiogenesis focus solely on endothelial cells (EC), however, RA fibroblast like synoviocytes (FLS) also contribute to this process. Therefore, a model including both EC and RA FLS would be more representative of synovial angiogenesis. Previous work demonstrates that the non-canonical NF-κB pathway with its main regulator NF-κB inducing kinase (NIK), induces angiogenesis in EC. Yet, this still remains to be studied in a co-culture model. Objective: Generate a 3D model of RA synovial angiogenesis and study effects of non-canonical NF-κB signalling, RA synovial fluid (RASF) and inhibitors on angiogenesis. Methods: We developed a 3D model in which HUVEC and RA FLS labelled with green or orange cell tracker dye, respectively, were incubated overnight to form spheroids. Subsequently, spheroids were harvested and plated in a collagen solution, and medium with or without lymphotoxinα1β2 (LT) or LIGHT (activators of non-canonical NF-κB signalling) or growth factors (bFGF/VEGF) was added. After 48 h, spheroids were fixed and imaged through confocal microscopy. Cumulative EC sprout length was quantified using Leica QWin Plus software. To demonstrate NIK dependency, EC were transfected with non-targeting or NIK-targeting siRNA before incorporation into the model. In addition, spheroids were incubated with RASF, with or without inhibitors, and subsequent changes in sprout formation were measured. Results: Confocal analysis of the 3D model showed spheroids formed sprouts under all conditions. LT and LIGHT caused significant increases in cumulative sprout length (p < 0.05). LTβR-induced sprout formation was significantly decreased by siRNA-mediated knockdown of NIK in EC as compared to the non-targeting controls. RASF induced sprout formation at all concentrations with a significant increase observed at 10%. This sprout formation was significantly decreased in the presence of different inhibitors of angiogenesis. Conclusion: The 3D model is an effective tool for studying RA angiogenesis. This novel model incorporates two key cellular mediators of this process, EC and RA FLS, and true capillary-like structures are formed that can be easily quantified. Using this system, we have demonstrated that activation of the non-canonical NF-κB pathway induces angiogenesis in a NIK-dependent fashion. Therefore, targeting NIK may have therapeutic potential in reducing pathological angiogenesis and halting disease progression. Further studies testing the efficacy of NIK inhibitors are currently underway. Additionally, we have demonstrated that RASF is a potent inducer of angiogenesis in the 3D model and that this can be used to measure the effectiveness of pharmacological inhibitors of angiogenesis.